LITERATURE REVIEW ANALISIS PERMINTAAN KB DI KOTA PADANG (STUDI KASUS RUMAH TANGGA MISKIN) - Maryetti; Abdullah, Dessy (Yayasan Nusantara Hasana Berdikari, 2025)
The Family Planning (FP) program aims to control population growth and improve family welfare. Despite the government's subsidized FP services, participation from low-income households in Padang City remains limited. The demand for FP services among low-income households is hindered by various factors, with economic conditions being the primary obstacle. This article employs a literature review approach to analyze the factors influencing the demand for the FP program among low-income households in Padang City. Data were collected from various sources, including journal articles, government reports, and previous research relevant to this topic. The analysis was conducted by organizing the findings into key themes: economic, social, cultural factors, and government policies. Economic factors were identified as the primary barrier to access for low-income households to FP services. Indirect costs such as transportation and limited healthcare facilities were significant obstacles. Additionally, social and cultural factors, including community norms that place value on having many children, further hindered the adoption of the FP program. Although government policies have provided subsidies, they have not been fully effective due to a lack of understanding regarding the variety of contraceptive methods available. The findings suggest that, although various policies have been implemented, the challenges faced by low-income households in Padang City are more complex and require a more holistic approach. To increase participation, more inclusive policies are needed that consider social and cultural factors, along with improving the accessibility of FP services in remote areas.